Indonesia’s Trade Sovereignty and the U.S. Poison Pill Clause in International Law - Gunawan, Yordan; Wirayudha, Dimas Putra; Akbar, M. Fabian; Khaer, Fawaz Muhammad (Faculty of Law, Jambi University, 2025)
This article examines how the United States' poison pill clause will effect Indonesia's ability to establish trade deals in the future. The primary inquiry is whether the language, initially incorporated into USMCA Article 32.10, aligns with Indonesia's rights and obligations under international economic law. The article contends that poison pill clauses, ostensibly designed as trade limitations, operate as constraining treaty mechanisms that could impair a state's ability to establish agreements with third nations. This research employs a doctrinal legal methodology based on normative analysis, utilizing treaty interpretation and comparative legal frameworks in accordance with the Vienna Convention on the Law of Treaties and pertinent WTO principles. This includes checking for any concerns with Indonesia's regional commitments and the possibility that they will make it harder to trade over time. The main point is that poison pill clauses make it hard for countries to respect the rules of treaty freedom, sovereign equality, and consistency in the international trading system. There are significant legal grounds for Indonesia not to make such harsh requirements in future trade agreements. Other countries that are becoming more powerful or are already powerful and have complicated treaty responsibilities may likewise have comparable concerns.